2014
DOI: 10.1007/s00266-014-0426-z
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Embolic Channel Causing Blindness Following Filler Injection

Abstract: Under some specific conditions favoring embolism, persistent interarterial anastomoses between the face and the eye allowed filler emboli to flow into the globe causing ocular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 11 publications
0
30
0
1
Order By: Relevance
“…20-1000 µm), it may become lodged, causing distal tissue necrosis. (2) If hyaluronic acid embolism occurs, there is a chance that it can be dissolved by hyaluronidase administration within the window period of 60-90 minutes. (11) …”
Section: Immediate Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…20-1000 µm), it may become lodged, causing distal tissue necrosis. (2) If hyaluronic acid embolism occurs, there is a chance that it can be dissolved by hyaluronidase administration within the window period of 60-90 minutes. (11) …”
Section: Immediate Actionmentioning
confidence: 99%
“…(1) Very rarely, severe complications such as skin necrosis, visual loss and stroke have been reported. (2) It is believed that these events are caused by accidental intravascular administration of filler material leading to ischaemia or infarction distal to the point of entry.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, according to the actual experience of many clinicians, a retrograde embolization mechanism was widely accepted. In 2015, the specific mechanism of retrograde embolism was discussed in detail in Tansatit's article [13,14]. Using a dye, human bodies were perfused through both the superficial temporal artery and the facial artery, and the dye came out from the globes.…”
Section: Discussionmentioning
confidence: 99%
“…To verify the retrograde embolism theory, Tanvaa et al [13,14] carried out experiments on corpses. They demonstrated that the injectant reached the ophthalmic artery system from the facial artery in most of the experimental cadavers under a certain injection pressure, which heightened the surgeons' concerns about the risk of facial filling.…”
Section: Introductionmentioning
confidence: 99%
“…9,10,11 The nasolabial and the frontotemporal units are known to be danger zones due to large-core cutaneous arteries susceptible to accidental cannulation, the facial and the superficial temporal arteries. 12 Young patients may have higher risk of blindness because healthy skin has abundant cutaneous arterial anastomoses. If the patient complains of sudden ocular pain or visual loss, however, injection must cease immediately.…”
Section: Intra-arterial Embolismmentioning
confidence: 99%